A geografia da industria de lanificios na Uniao Europeia - Pires, I. M. (2021)
In the production of woollen textiles, unlike cotton, the competition is mainly from industrialised countries. The textiles are normally produced in small quantities, incorporating design and frequently adapted to fashion, therefore preventing mass consumption. The need for qualified and skilled workforce prevents the relocation to countries that can only offer low wages. Thus the EU maintains its world leading position as wool textile producer, the dominant role belonging to Italy, Germany and France. Another important feature is specialisation of each of these countries in a specific segment of the wool filiere. Over the last few years the distribution of wool products among the EU countries has been growing and they still trade mostly amongst themselves. Consequently, the productive space has become more cohesive with a simultaneous reinforcement of the centre-periphery model.